Force Tools (Excel 97-2003): EEE-Model for Monte Carlo simulations - Romero Rojo, Francisco Javier (Cranfield University, 2019)
See links to relevant papers for further information.
Keywords: 'Cost engineering'; 'Manufacturing'; 'Obsolescence'; 'EEE-FORCE'; 'M-FORCE'; 'Manufacturing Engineering not elsewhere classified'